Acceptance, hesitancy and refusal towards COVID-19 vaccination - Asavari Raut; Abdul Samad; Jay Verma; Pranad Kshirsagar (Elsevier, 2023)
Problem: The determinants of COVID-19 vaccine acceptance, hesitancy, and refusal remain poorly understood. We assessed the general population of Pune after visiting tertiary care hospital for their willingness to accept the vaccine and the reason for their hesitancy and refusal. Methodology: A six-month descriptive cross-sectional study with 386 community members over the age of 18 who visited the Tertiary Hospital OPD was conducted. The vaccine acceptance and hesitancy was assessed using a self designed detailed questionnaire with a one-time face-to-face interview. Results: Acceptance for vaccine was observed in 235 (60.8%) participants, while 151 (39.2%) hesitated and refused. Participants with lower education (P < 0.00001), no employment did not readily accept the vaccine (P < 0.00001). Pregnant, breast-feeding women (21.8%) hesitated vaccine because of lack of evidence regarding vaccine safety. Participants (73.6%) were readily accepting (third dose) booster dose of vaccine when available. The reason for vaccine hesitance was the concern about side effects (58.2%) and reason for acceptance was to get immunity against COVID-19 (76.1%). Vaccine information source appears to be an influential aspect, as participants who obtained vaccination information from healthcare providers had no concerns regarding vaccination. Conclusion: The study has found a link between average education level, unemployment and vaccine acceptance and hesitancy. Factors influencing vaccine hesitancy include lack of vaccine information, vaccine side effects, and misinformation spread via social media. Clinical pharmacists can play an important role in boosting up vaccine acceptance by providing appropriate information in community.